REPERTÓRIO MOTOR NO PERÍODO DE FIDGETY MOVEMENTS EM LACTENTES EXPOSTOS A INFECÇÕES POR TORCHS - Sarita Baltuilhe dos Santos (2022)
Introduction: TORCHS are a group of infections acquired during pregnancy or during childbirth with similar clinical manifestations that can impair the normal course of development. Despite its epidemiological importance, no studies were found that investigated neuromotor behaviors in intants exposed to TORCHS infections. Assessment of general movements (GMs), especially between 3-5 months of post-term age (period of fidgety movements – (FMs), has a high predictive value for neurological impairment. Objective: To investigate the quality of GMs and the motor repertoire in the period of fidgety movements in infants exposed to maternal infection by TORCHS, checking the association of clinical characteristics and risk factores on the observed outcomes. Method: This exploratory observational study comprise a convenience sample of 17 infants (age 53,6±3,0 weeks post-term) with confirmed prenatal exposure to TORCHS, recruit from local referral centers. Infants were evaluated Only once, using the General Movements Assessment (GMA) tools for the quality of GMs and the Motor Optimality Score (MOS) to assess details of movement patterns, postural patterns and movement characteristics in this phase. Clinical data and risk factors (weight at birth, prematurity, etiologic agente, imaging tests, among others) were also collected. Results: Five infants (29.4%) had abnormal FMs in the GMA assessment. No Cramped-synchronized movements were observed. The majority (87.5%) of the infants had a reduced total MOS score [23,5 (21-26)]. Only 2 (12.5%) infants had smooth and fluente movements. In movement patterns, all observed tongue movements and head rotation were abnormal, in posture patterns, abnormal symmetrical movements and abnormal predominant fisting and finger spreading were observed, almost all were abnormal, especially jerky and monotonous, in the assessment of movement characteritics. Only the total MOS score was associated with prematurity. Conclusion: Infants present abnormalities in the quality of FMs and in the motor repertoire during the FMs period, wit minimal interference from risk factors.